Harnessing Green Nitrogen-Doped Zinc Oxide for Efficient Methylene Blue Dye Photocatalytic Degradation in Wastewater Treatment - Ummu Humairah Hashim; Shahzulaikha Aiman Mohmed; Syahida Suhaimi; Maisurah Mukhtar; Nur Athirah Mohd Taib; Imam Tazi (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 1 Page (86–94)